2020
DOI: 10.3390/jcm9040914
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Exercise Training on Brain Structure and Function in Older Adults: A Systematic Review Based on Evidence from Randomized Control Trials

Abstract: Accumulating evidence suggests that exercise training is associated with improvements in brain health in older adults, yet the extant literature is insufficient in detailing why exercise training facilitates brain structure and function. Specifically, few studies have employed the FITT-VP principle (i.e., Frequency, Intensity, Time, Type, Volume, and Progression) to characterize the exercise exposure, thus research is yet to specify which characteristics of exercise training benefit brain outcomes. To determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 58 publications
(298 reference statements)
4
47
0
Order By: Relevance
“…In addition, the influence of confounding effects of fatigue, attention, emotional arousal, and motivation on both behavioral and neurophysiological aspects of inhibition are often not considered. Specifically, Chen et al [ 116 ] suggested that researchers should characterize exercise training using variables such as frequency of training, intensity, duration, type of training, volume of training, and progression. For acute exercise, some of those variables are irrelevant (e.g., frequency and volume) but researchers would do well to include as many characteristics as possible of the exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the influence of confounding effects of fatigue, attention, emotional arousal, and motivation on both behavioral and neurophysiological aspects of inhibition are often not considered. Specifically, Chen et al [ 116 ] suggested that researchers should characterize exercise training using variables such as frequency of training, intensity, duration, type of training, volume of training, and progression. For acute exercise, some of those variables are irrelevant (e.g., frequency and volume) but researchers would do well to include as many characteristics as possible of the exercise intervention.…”
Section: Discussionmentioning
confidence: 99%
“…For acute exercise, some of those variables are irrelevant (e.g., frequency and volume) but researchers would do well to include as many characteristics as possible of the exercise intervention. As Chen et al [ 116 ] suggested, this would allow us to better understand which exercise characteristics affect brain function.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are no data available regarding HT recipients. These benefits on cerebrovascular function may explain the positive impact of exercise on cognition, including benefits on learning, memory, attention and executive functions in healthy adults [ 55 , 56 ] and HF patients [ 38 , 57 , 58 ]. The positive beneficial effect of exercise training on cognitive function is likely due to its pro-neurogenic effects [ 59 ].…”
Section: Discussionmentioning
confidence: 99%
“…The positive beneficial effect of exercise training on cognitive function is likely due to its pro-neurogenic effects [ 59 ]. Some evidence also revealed that regular exercise may increase angiogenesis, neurogenesis, synaptogenesis and neurotransmitter synthesis in cerebral structures, as well as increasing grey and white matter volume [ 35 , 55 ]. The increased cerebral flow, especially after transplant [ 60 ], could stimulate neurobiological mechanisms leading to an improvement in cognitive function.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, physical exercise and physical training lead to changes on (i) molecular and cellular levels (e.g., brain-derived neurotrophic factors), (ii) structural and/or functional levels (e.g., hippocampus volume and hippocampal activity), and (iii) socioemotional level (e.g., sleep quality, well-being, self-efficacy) 22 . Currently, there are systematic reviews and meta-analysis available which summarize the beneficial effects of acute physical exercise (a single bout of exercise) on changes: (i) molecular and cellular level (i.e., brain derived neurotrophic factor) 2326 , (ii) structural level 27,28 and (iii) socioemotional level (i.e., sleep) 29,30 . In contrast the effects of exercise on functional brain changes that accompany acute physical exercise and chronic exercise intervention are currently less well understood.…”
Section: Introductionmentioning
confidence: 99%